Pengembangan modul hands on mathematics berbasis review jurnal untuk mendorong keterlibatan siswa dalam kurikulum merdeka - Kusumawati, Ratih; Hidayati, Destia Wahyu; Kurniati, Lenny (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
The massive development of technology in education has led to the implementation of digital-based learning. However, the impact of the pandemic and the implementation of online learning by utilizing digital technology has caused problems in the form of learning loss. The Merdeka Curriculum as an effort to resolve this learning loss has actually created new problems, that is, teachers' difficulties in implementing differentiated, fun, and meaningful student-centered learning. More specifically, this difficulty occurs for math teachers who do not have references to various mathematics activities that support meaningful learning. One alternative solution to solve this problem is to have a special module that contains references to various mathematical activities and games. The purpose of this research is to develop a hands-on mathematics module based on journal studies which becomes a teaching module in the manipulative mathematics media course. The research and development model to be implemented is 4D Thiagarajan which consists of 4 stages, these stages are define, design and develop. The dissemination stage was not carried out in this period due to research limitations. The results showed that the developed module met the validity criteria with a score of 2.71, met the practicality criteria with a score of 87% and met the effectiveness criteria with a score of 91,6. It’s concluded that the hands on mathematics module was feasible to use and met the criteria of valid, practical, and effective. The results of the study are expected to be a recommendation for further development research and for teachers in designing mathematics learning.